When Financial Institutions Are Large Shareholders: The Role of Macro Corporate Governance Environments - LI, DONGHUI; MOSHIRIAN, FARIBORZ; PHAM, PETER KIEN; ZEIN, JASON (Journal of Finance, 2006)
ABSTRACT While financial institutions' aggregate investments have grown substantially worldwide, the size of their individual shareholdings, and ultimately their incentive to monitor, may be limited by the free‐rider problem, regulations, and a preference for diversification and liquidity. We compare institutions' shareholding patterns across countries and find vast differences in the extent to which they are large shareholders. These variations are largely determined by macro corporate governance factors such as shareholder protection, law enforcement, and corporate disclosure requirements. This suggests that strong governance environments act to strengthen monitoring ability such that more institutions are encouraged to hold concentrated equity positions.